Towards a Corpus-based Collocations Dictionary of Modern Standard Arabic - Izwaini, Sattar (2025)
This paper discusses the need to compile a collocational dictionary of modern standard Arabic. It reports a project under way of producing a corpus-based dictionary of Arabic collocations. It outlines the corpus composition, the electronic tools used, and the guidelines followed in the carrying out the project. The paper describes the evolution and progress of the project. It will also discuss other linguistic features of words and their collocations such as number, gender, and syntactic configurations